2009
DOI: 10.1253/circj.cj-08-1147
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Electrocardiograms for Patients With Non-ST-Segment Elevation Acute Coronary Syndromes in the Interventional Era

Abstract: Circ J 2009; 73: 798 -805 atients with non-ST-segment elevation acute coronary syndromes (NSTE-ACS) are heterogeneous with regard to both the underlying pathophysiology and the future risk of cardiac events. 1 Early risk stratification is crucial for appropriate management of this condition and for deciding whether early invasive strategies should be adopted. 2 Because of its simplicity, safety, widespread availability and low cost, the electrocardiogram (ECG) has been extensively used for risk stratificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…46 In this review, we discussed various pathological characteristics of anterior wall STEMI on the basis of the ECG findings. We hope this will contribute to the optimal use of these findings in clinical practice, taking into account inherent limitations of the technique.…”
Section: Discussionmentioning
confidence: 99%
“…46 In this review, we discussed various pathological characteristics of anterior wall STEMI on the basis of the ECG findings. We hope this will contribute to the optimal use of these findings in clinical practice, taking into account inherent limitations of the technique.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown similar baseline and clinical characteristics in the ST-segment depression group. [4,5] In particular, these comorbidities in the ST-depression group and the no ECG change group were more distinct than those seen in previous studies, [4,5] which may suggest that our study population is a real-world practice, including more high-risk patients than other randomized studies. However, some studies [6,7] reported that hospital mortality increased as the number of cardiovascular risk factors declined.…”
Section: Discussionmentioning
confidence: 73%
“…29,30 A standard 12-lead ECG on admission is the initial and most widely used method for early risk stratification in patients with NSTE-ACS. 31 Our study showed that QRS prolongation and ST-segment elevation in lead aVR on admission (especially the former) are useful for predicting LM/3VD and can thereby facilitate decision-making, that is, patients likely to have LM/3VD should promptly undergo an angiography and not receive clopidogrel therapy to allow early CABG. Our results emphasize the importance of analyzing QRS duration as well as ST-segment deviation on the admission ECG in the diagnostic workup of patients with NSTE-ACS.…”
Section: Discussionmentioning
confidence: 83%